A research on the effect of cutting parameters on cutting force in flat grinding using segmented grinding wheel - Phuong, Nguyen Thi; Phuong Giang, Nguyen Thi; Dong, Nguyen Tien (Vietnam Journal of Science and Technology, 2017)
This article represents the result of a research on the impact of cutting parameters including the number of segments, cutting depth and feed rate on cutting force P when grind SKD11 harden steel using bevel segment grinding wheel using Taguchi method and analysis of variance (ANOVA). The result release the information of the relationship between the number of segments, cutting depth and feed rate and its interactions with cutting force. Local optimal value of cutting force can also be determined with minimal cutting force and low surface roughness when machining the SKD11 harden steel using bevel segment grinding wheel.